FORMATION AND DEVELOPMENT OF COGNITIVE INTERESTS IN STUDENTS IN MOTHER TONGUE AND LITERATURE (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article focuses on the importance of cognitive education in shaping students' interest in their native language and literature.